Models of grinding-induced surface and subsurface damages in fused silica considering strain rate and micro shape/geometry of abrasive. Issue 17 (1st September 2021) - Xiao, Huapan; Yin, Shenxin; Wang, Hairong; Liu, Yuhu; Wu, Heng; Liang, Rongguang; Cao, Huajun
Abstract: Based on the indentation fracture mechanics of brittle material, the correlations between the subsurface crack depth and the scratch depth induced by pyramidal, conical, and spherical indenters are established, respectively. Combined the kinematics of grinding process, the theoretical models of surface damage (SD) and subsurface damage (SSD) depths are developed considering the strain rate effect and the micro shape/geometry of abrasive grit. The mechanical properties of fused silica under different strain rates are measured by nanoindentation test. Many fused silica samples are processed under different grinding parameters, and their SD and SSD depths are measured. In combination with the experimental results, the theoretical models from differently shaped grits are assessed, and the effects of grinding/abrasive grit parameters are analyzed theoretically. The results show that compared with experimental SD and SSD depths, those calculated from spherical or pyramidal grit have average errors of less than 11.0% and 6.0%, respectively, while those from conical grit have average errors of more than 50.0% and 33.0%, respectively. The models from hybrid grit can be used to predict the SD and SSD depths efficiently, with average errors of 5.3% and 4.6%, respectively. The results also show that both SD and SSD depths increase with the grit apex angle, diameter, tip radius, or extraction depth. Moreover, the strain rate decreases with increasing grinding depth, feed speed, or grit diameter. The research is useful to optimize the grinding/abrasive grit parameters to reduce the damages in ground brittle materials.